Problems and possible ways to improve the criminal law protection of lands (Journal of actual problems of jurisprudence, 2018)
This article analyzes the main challenges of bringing to legal liability associated with both the conflicting provisions of regulations as well as with law enforcement. Attention is paid to the study of ways improve the legislation. At the present stage in need of serious scientific analysis of issues such as the definition of the boundaries of administrative and criminal liability for damage to land, questions of qualification of acts encroaching on the land. An analysis of the criminal legislation of certain foreign countries with a view to the possible use of foreign experience in improving the article 273 of the Criminal Code of the Kyrgyz RepublicKey words: land damage, land, criminal liability, law and order.